Політична програма махновського руху. (Zaporizhzhia Historical Review, 2021)
In the given article the author investigates the development of the political conceptions of Makhno’s rebels in 1917- 1921 and describes the content and main ideas of their program documents. It is stressed that Makhno’s political program failed to escape the elements of utopism which is explained by lack of time for practical check-up of its theoretical grounds.